1971
DOI: 10.1128/jb.108.3.1065-1071.1971
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of the Inhibition of Cardiolipin Metabolism in Haemophilus parainfluenzae

Abstract: Examination of phospholipid metabolism in Haemophilus parainfluenzae with inhibitors of various cellular functions-indicated that macromolecular synthesis and lipid metabolism can be dissociated at least for a short time. Two classes of inhibitors have relatively specific effects on cardiolipin (CL) metabolism. Pentachlorophenol and p-hydroxymercuribenzoate blocked CL synthesis but allowed CL hydrolysis to phosphatidic acid and phosphatidyl glycerol (PG); 3,3',4,5'-tetrachlorosalicylanilide (TCS) and carbonyl … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
0

Year Published

1972
1972
2007
2007

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 25 publications
3
19
0
Order By: Relevance
“…In comparison with wild-type cells, the most relevant phenotype of the cls mutant strain was its increased sensitivity to exposure to toxic compounds that are eliminated from the cell via RND (resistance, nodulation, cell division) efflux pumps. This is in agreement with the pioneering observation made in Dr White's laboratory that inhibition of CL synthesis in Haemophilus parainfluenza by certain drugs interfered with their extrusion by interrupting energy-dependent transport systems (Ono and White, 1971). In this regard phospholipids have been shown to play an important role in the stabilization of protein complexes, in protein folding and insertion in the membranes, translocation across membranes, and orientation of transmembrane domains within the membrane (Kusters et al, 1991;Klompenburg et al, 1998;Bogdanov et al, 2002;Zhang et al, 2002;Pfeiffer et al, 2003).…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…In comparison with wild-type cells, the most relevant phenotype of the cls mutant strain was its increased sensitivity to exposure to toxic compounds that are eliminated from the cell via RND (resistance, nodulation, cell division) efflux pumps. This is in agreement with the pioneering observation made in Dr White's laboratory that inhibition of CL synthesis in Haemophilus parainfluenza by certain drugs interfered with their extrusion by interrupting energy-dependent transport systems (Ono and White, 1971). In this regard phospholipids have been shown to play an important role in the stabilization of protein complexes, in protein folding and insertion in the membranes, translocation across membranes, and orientation of transmembrane domains within the membrane (Kusters et al, 1991;Klompenburg et al, 1998;Bogdanov et al, 2002;Zhang et al, 2002;Pfeiffer et al, 2003).…”
Section: Discussionsupporting
confidence: 84%
“…Changing the proportions of anionic phospholipids may alter some of the divisional processes, which could lead to cell division before the cell has reached the average size of the wild-type cells. Several reports have suggested that CL participates in resistance to several stresses such as starvation, toxic chemicals, heat or saline environments (Ono and White, 1971;Hiraoka et al, 1993). However, P. putida DOT-T1E cls mutants were not more severely affected than the wild type by most of the different stresses we tested.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…This proposal by Bernal and colleagues (2007) is based on the fact that the rate of accumulation of ethidium bromide in P. putida cls mutant cells was higher than in wild-type cells. The observation that the functioning of efflux transporters could be influenced by bacterial phospholipid composition was already envisaged by White's group some 30 years ago (Ono and White, 1971). Consistent with the rigidity studies described above, our present results show that the entry of ethidium bromide into carbonyl cyanide 3-chlorophenyl hydrazone-treated cti mutant cells was 1.4-fold faster than in the parental strain, whereas the rate of entry in the cls mutant was 1.4-fold slower, and the introduction of a cls mutation into the cti mutant produced a compensatory effect, so that the rate of entry was similar to that determined for the wildtype strain.…”
Section: Decreased Extrusion Of Ethidibum Bromide In Mutants Deficienmentioning
confidence: 93%
“…The hydrophobic 820 diglyceride ends seem to be metabolically stable, but the glycerol diphosphate in the middle undergoes rapid synthesis and hydrolysis from a small portion of the phosphatidylglycerol (PG) pool in H. parainfluenzae and Staphylococcus aureus (20,27). Inhibitors of oxidative phbsphorylation and proton gradient formation, like carbonylcyanide-chlorophenolhydrazone (m-CCCP) or tetrachlorosalicylanilide, inhibited an activity coupled to the rapid metabolism of CL but had no effect on the isolated phospholipase D in vitro (16). The unique localization of CL in the inner membrane of the mitochondria and the fact that the rapid metabolism of CL in bacteria was coupled to components in the membrane involved in oxidative phosphorylation suggested some possible role for CL in the electron transport system.…”
mentioning
confidence: 99%